Bowenoid Papulosis A Case Report - Handelia Phinari; Ni Nyoman Ayu Sutrini (Fakultas Kedokteran UPN Veteran Jakarta Kerja Sama KNPT, 2022)
Bowenoid papulosis (BP) is a rare case of sexually transmitted disease caused by Human Papillomavirus 16 that affects the young, sexually active age group. A 39-years-old male complained of warts over the scrotum and left groin that gradually increased in number and size for one year duration. There was history of similar complaint. Dermatology status obtained multiple, small, well-defined, grey-brown papules on the scrotum and left groin. Dermoscopy examination revealed a pigmented papillomatous surface, brown-grey dots linearly arranged at the edges, and widespread dotted vessels. Histopathological examination confirmed Bowenoid Papulosis. Based on the clinical findings, Bowenoid papulosis cannot be distinguished from Condyloma Acuminata. Therefore, histopathological examination is necessary to confirm the diagnosis. The patient is treated with surgical excision and cauterization. Six months after the procedure, the patient had no complaints or new lesions. Since the development of BP is unpredictable, early diagnosis, adequate treatment, and routine examinations for recurrence and progression of the disease are required.